Risk of postoperative urinary retention after sugammadex use in laparoscopic hernia repair: A matched cohort study of 23,444 cases - Kuo-Chuan Hung; Hsiu-Lan Weng; Yi-Chen Lai; Jheng-Yan Wu; Ping-Hsin Liu; Kuei-Fen Wang; I-Wen Chen (PLoS ONE, 2025)
Purpose This study aimed to determine whether sugammadex use is associated with lower postoperative urinary retention (POUR) incidence than neostigmine-glycopyrrolate reversal in patients undergoing laparoscopic hernia repair. Methods This retrospective cohort study used the TriNetX research network database to analyze adult patients who underwent laparoscopic hernia repair. Patients receiving rocuronium/vecuronium were divided into sugammadex (n = 92,543) or neostigmine-glycopyrrolate (n = 11,723) reversal groups. After 1:1 propensity score matching, 11,722 matched pairs were analyzed. The primary outcome was POUR within 30 days. The secondary outcomes included pneumonia, hospital readmission, and emergency department (ED) visits. Subgroup analyses were used to examine the effects of age and sex. Results In the matched cohort (n = 23,444), sugammadex was associated with a significantly lower risk of POUR (OR 0.23, 95% CI 0.18–0.31; p < 0.001) and ED visits (OR 0.76, 95% CI 0.66–0.87; p < 0.001). No significant differences were found in pneumonia or readmission rates. The POUR reduction was consistent across sexes (males: OR 0.32; females: OR 0.33) but more pronounced in patients aged >50 years (OR 0.35) than in younger patients (OR 0.50, p = 0.067). Among male patients receiving sugammadex, older age (OR, 1.01), history of urinary retention (OR, 9.94), and benign prostatic hyperplasia (OR, 4.04) were significant independent risk factors for POUR. Conclusions Sugammadex use is associated with a 77% reduction in POUR and 24% fewer ED visits than neostigmine following hernia repair, suggesting that it may be the preferred reversal agent, particularly for older adults who gain the most benefit.